Estimation of R404A Refrigerant Cooling Load and System Efficiency of a Small-Scale Cold Box for Strenghten The Fisheries Cold Chain in Timbolsloko, Demak - Hanityo Adi Nugroho; Samsudi R; Rubijanto JP; M. Ahnaf F; Aulia SS; Aditano YR (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2026)
The cooling system of the fishing boat is extremely crucial in maintaining the quality of the catch during storage. In this study, the system performance and cooling load are analyzed in a box of dimensions 1.8 m × 2.4 m × 1.2 m with R404A refrigerant at an evaporation temperature of -21.8°C and a condensation temperature of 37.6°C. Total daily cooling load is 15.504 kWh, which includes heat transmission load of 5.653 kWh, product load of 6.656 kWh, internal load of 0.542 kWh, equipment load of 1.61 kWh, and infiltration load of 1.043 kWh. System performance by pressure-enthalpy (P-h) analysis provides actual Coefficient of Performance (COP) as 4 with 94% refrigeration efficiency. The 100 mm polyurethane insulation utilized are enhance energy efficiency and environmental sustainability. This cooling system design was found to be optimal for maintaining the box temperature at -20°C with high efficiency, serving to benefit the small-scale fisheries sector under tropical conditions.